Portuguese Presidency of the Council of the European Union - Conference on Access to Medicines and Medical Devices - silva, raquel (2021)
Within the scope of the Portuguese Presidency of the Council of the European Union, the 3 A’s (Availability, Accessibility, Affordability) International Conference was organized with the aim of defining priorities and policy options that will translate into concrete actions related to access to medicines and medical devices across the European Union. The Conference took place on April 29th and 30th, at Centro Cultural de Belém, in Lisbon. This document presents a summary of the topics discussed at the Conference. Additional information about the Conference can be found at: https://ppeu2021.infarmed.pt/pt/events/conferencia-3as.